P530 Proactive therapeutic drug monitoring of anti-TNF agents is associated with higher mucosal healing rates in Crohn's disease. (27th May 2021) - Brinar, M; Sabic, M; Turk, N; Grgic, D; Domislovic, V; Cukovic Cavka, S; Kozmar, A; Krznaric, Z
Abstract: Background: Reactive therapeutic drug monitoring (TDM) is routinely used in managing secondary loss of response to anti-TNF agents. Proactive TDM use has been associated with better clinical outcomes but its use in routine practice is still controversial. We aimed to investigate whether using proactive TDM strategy will result in higher mucosal healing and clinical remission rates. Methods: After review of electronic case files, all patients that received anti-TNF treatment for active disease from 01.01.2017-01.02.2021. and responded to induction were included. Patients starting treatment for postoperative prophylaxis were excluded from the study. In the proactive group TDM was performed in week 14 and patients with subtherapeutic trough levels were dose optimized and underwent subsequent TDM measurments until the target trough level was reached. In the reactive group TDM was performed in the case of loss of response. Mucosal healing was defined as SES CD 3 for patients with CD and Mayo endoscopic score of £ 1 for UC patients. Clinical remission after 52 weeks was defined by the attending physician. Results: A total of 161 IBD patients were included, 109 patients with CD and 52 patients with UC. There were 69 patients in the proactive group and 92 patients in the reactive group. No significant difference regarding age at diagnosis, age at treatment initiation, disease duration, prior immunomodulator use and time do endoscopy was observed between groups. A higher proportion of patients in the proactive group achieved mucosal healing but the difference between groups was not significant in the total cohort (proactive 52.4% vs reactive 42.2%; p=0.250). A significantly higher proportion of CD patients (n=109) in the proactive group achieved mucosal healing compared to the reactive group (56.8% vs 34.8%; p=0.039). No significant difference in mucosal healing rates between the groups was observed in UC cases. No significant difference in clinical remission rates was observed between the proactive and reactive group in the total cohort, CD and UC patients respectively. Conclusion: Proactive TDM strategy is a valuable tool in managing CD patients resluting in higher rates of mucosal healing. Further studies are needed to define the optimal timepoints for proactive TDM.